The Prevalence of Physical Disability in Elderly SAMPLE in Primary Health Care Centers (PHCs) in AL-Resafa Sector /Baghdad/2018 - Hassan, Rana A.; Hasan, Lamyaa Ali (Journal of the Faculty of Medicine Baghdad, 2020)
Background The proportion of older population throughout the world is continuously increasing, and becomes a challenge worldwide, since it may lead to an increasing number of disabled populations, and to a rise of the national health burden, and so there is greater need to look into their physical disability aspects, which is otherwise neglected. Objectives To estimate the prevalence of Activity of Daily Living dependency(ADL) in primary health care centers(PHCs) in AL Resafa health sector in Baghdad, and to find association between dependency and some sociodemographic factors. Method A Descriptive cross- sectional study was carried out in all PHCs in AL Resafa health sector in Baghdad and 250 elderly were interviewed using pretested questionnaire which covered some Sociodemographic factors and Barthal index scale( a 10 item instrument measuring functional independence in personal Activities of Daily Living). Results 250 participants all of them are aged 60 year and older, those aged 60 to 69 years were 47.6%, minority aged 80 years and older , elderly female were slightly more than male (51.6%,48.4% ), Most of participants 97.6% were living in company with their families, 82.0% were not currently employed, 48% overweight , According to Barthal index scale score: 78.0% were independent while ADL with assistance observed in 15.2% and those of ADL with severity 6.8%. There was a significant association between increase in age, Female gender, low education and obesity with decrease in ADL. Conclusion Preserving functional capacity of elderly is a great challenge to public health, subjects categorization on the basis of Barthel index to correlates functional disability will be of value for a better quality of life.